FAHM AL-HADITH WITH THE ANTROPOLOGICAL APPROACH: The Study of Hadith La Yazalu Hadha al-Amr fi Quraish - Azhar, M. Fahmi (RIWAYAH, 2023)
Understanding hadith correctly is an important aspect of the pattern of interaction with the hadith of the Prophet. The appropriate understanding process will also produce the correct understanding of hadith. Anthropology is a science that studies humans from their physical diversity and study human culture such as ways of behaving, cultures and the resulting values. Anthropological studies focus on studying humans and their horizons. This research uses a type of literature study which emphasizes aspects of literature related to the study being discussed. The results of this research show that the study of understanding hadith approaches using Anthropology is based on the strong relationship between religion and culture because it is impossible for hadith texts to be born in an empty space, so this study can be a solution to various contemporary problems that may be affecting the sound of the text in question. Finally, in applying an anthropological approach in understanding the hadith regarding the appointment of leaders who must be from the Quraysh tribe, concludes that there is a cultural internalization of the intellectuals of the Prophet Muhammad so if it is contextualized today, the Quraysh tribe in question is a symbol of the skills and capabilities of a leader.